FORMATION OF THE PREPUTIAL CAVITY OF THE PENIS OF ONE HUMPED CAMEL - Mahdi; A. Atyia (Basrah Journal of Veterinary Research)
The present work was down on the penises of immature camel of 3-36 month of age. This work is done to investigate the stepes and method of the separation between the free end of the penis and its sheath to forming the preputial cavity.